(untitled) (Damascus University Journal of educational and Psychologyical sciences, 2025)
This study aimed to uncover the extent to which concepts of the Fourth Industrial Revolution are included in Information and Communication Technology (ICT) textbooks for basic and secondary education stages in the Syrian Arab Republic. To achieve the research objective, the two researchers adopted the descriptive methodology and prepared a content analysis form as a research tool. The results indicated that the textbook developers focused on teaching students programming skills and incorporating concepts related to application development, in addition to emphasizing the outputs of the Fourth Industrial Revolution, such as artificial intelligence and the Internet of Things, and preparing students for the job market by outlining the required qualifications and ways to access these jobs. However, a lack of inclusion of technologies such as virtual and augmented reality, nanotechnology, blockchain, cloud computing, and big data analysis was noted. The study recommended addressing this shortfall and conducting a descriptive study to observe the teaching of these textbooks in basic and secondary education schools.